Brentuximab Vedotin with Chemotherapy for Stage III or IV Hodgkin’s Lymphoma - Connors, J.M. (N Engl J Med, 2017)
BACKGROUND: Brentuximab vedotin is an anti-CD30 antibody–drug conjugate that has been approved for relapsed and refractory Hodgkin’s lymphoma. METHODS: We conducted an open-label, multicenter, randomized phase 3 trial involving patients with previously untreated stage III or IV classic Hodgkin’s lymphoma, in which 664 were assigned to receive brentuximab vedotin, doxorubicin, vinblastine, and dacarbazine (A+AVD) and 670 were assigned to receive doxorubicin, bleomycin, vinblastine, and dacarbazine (ABVD). The primary end point was modified progression-free survival (the time to progression, death, or noncomplete response and use of subsequent anticancer therapy) as adjudicated by an independent review committee. The key secondary end point was overall survival. RESULTS: At a median follow-up of 24.9 months, 2-year modified progression-free survival rates in the A+AVD and ABVD groups were 82.1% (95% confidence interval [CI], 78.7 to 85.0) and 77.2% (95% CI, 73.7 to 80.4), respectively, a difference of 4.9 percentage points (hazard ratio for an event of progression, death, or modified progression, 0.77; 95% CI, 0.60 to 0.98; P = 0.03). There were 28 deaths with A+AVD and 39 with ABVD (hazard ratio for interim overall survival, 0.72 [95% CI, 0.44 to 1.17]; P = 0.19). All secondary efficacy end points trended in favor of A+AVD. Neutropenia occurred in 58% of the patients receiving A+AVD and in 45% of those receiving ABVD; in the A+AVD group, the rate of febrile neutropenia was lower among the 83 patients who received primary prophylaxis with granulocyte colony-stimulating factor than among those who did not (11% vs. 21%). Peripheral neuropathy occurred in 67% of patients in the A+AVD group and in 43% of patients in the ABVD group; 67% of patients in the A+AVD group who had peripheral neuropathy had resolution or improvement at the last follow-up visit. Pulmonary toxicity of grade 3 or higher was reported in less than 1% of patients receiving A+AVD and in 3% of those receiving ABVD. Among the deaths that occurred during treatment, 7 of 9 in the A+AVD group were associated with neutropenia and 11 of 13 in the ABVD group were associated with pulmonary-related toxicity. CONCLUSIONS: A+AVD had superior efficacy to ABVD in the treatment of patients with advanced-stage Hodgkin’s lymphoma, with a 4.9 percentage-point lower combined risk of progression, death, or noncomplete response and use of subsequent anticancer therapy at 2 years. (Funded by Millennium Pharmaceuticals and Seattle Genetics; ECHELON-1 ClinicalTrials.gov number, NCT01712490; EudraCT number, 2011-005450-60.)